Factors associated with multi-drug-resistant tuberculosis in Dakar, Senegal, 2010-2016 - Mbouna Ndiaye; Pauline Kiswendsida Yanogo; Bernard Sawadogo; Fadima Diallo; Simon Antara; Nicolas Meda (AOSIS, 2020)
According to the World Health Organization, multidrug-resistant tuberculosis (MDR-TB) represents a major obstacle towards successful TB treatment and control. In Dakar, MDR-TB management began in 2010 with the strengthening of diagnostic resources. The objective of this study was to identify the factors associated with multidrug-resistant tuberculosis in Dakar between 2010 and 2016. We conducted a case-control study from January 10 to February 28, 2017 in tuberculosis centers in Dakar. of 169 cases and 507 controls. We used logistic regression with Epi-info version 7.2.1. to estimate the odds ratios of association. Factors significantly associated with MDR-TB were: residing in a periurban area (ORa=1.8; 95% CI (1.5-4.9); p=0.024), presence of MDR-TB in the entourage of patient (ORa=7.0; 95% CI (6.1-9.5); p=0.002), previous treatment failure (ORa=29.5; 95% CI (27.3-30.1); p=0.000), treatment not directly observed by a health care provider (ORa=4.3; 95% CI (4.1-7,2); p=0.000) and irregularity of treatment (ORa=1.7; 95% CI (0.5-5.4); p=0.037). Focusing interventions on population at-risk will prevent MDR-TB.